Effektivnost' trenirovocnogo meroprijatija po obšcefiziceskoj podgotovke v bazovoj podgotovke godicnogo cikla v greble na bajdarkach i kanoe - Vishnyakov, K.S. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article analyzes the feasibility of using the isolated training camp in general physical training in kayaking and canoeing in the annual cycle of the junior team of Russia up to 19 years. Significant increase in the results in the test for 2000m in water was recorded after a month of training only to the general physical fitness. Also, the negative impact on the special physical fitness of two consecutive physical training events for physical fitness conditions was recorded.